Factors influencing consumers' adoption of mobile financial services in Tanzania - Amina Abdinoor; Ulingeta O.L. Mbamba (Cogent Business & Management, 2017)
This study aimed at assessing consumers' adoption of mobile financial services in Tanzania using Technology Acceptance Model. The study had the following objectives, to assess the individual awareness of mobile financial services; perceived usefulness; perceived benefits; and costs effects on adoption of mobile financial services. Random sampling technique was employed to select the sample for data collection. Two hundred participants were selected randomly from Dar es Salaam region particularly Kinondoni District. The sample included the users and non-users of mobile financial services. The study used primary data and regression model. The findings of this study show that mobile financial service adoption is positively related to individual awareness, perceived usefulness and perceived benefit but it is negative related to cost effects. Nevertheless, the study showed that demographic characteristics of respondents (sex, age and income level) are among the factors moderating adoption of mobile financial services. From the findings, this study highlights recommendation that service providers need to play a leading role in influencing individual awareness, perceived usefulness, and perceived benefit of mobile banking. However, cost effect has been found as one of the barrier to the intention to adopt mobile financial services in Tanzania. Service providers should consider affordability and availability of the financial services for the low-income segment in the society. These results can be extended to any developing country.
Keywords: 650